Pengembangan Instrumen Kecemasan Belajar Fisika bagi Siswa SMA - Isran Mihardi; Supahar (Universitas Nurul Huda, 2026)
Physics learning anxiety is an affective factor that can influence students’ readiness to learn, concentration, and academic achievement. This study aimed to develop a valid and reliable instrument to measure physics learning anxiety among senior high school students. The development procedure followed the stages of research and development (R&D), including preliminary study, construction of dimensions and indicators, item development, content validation by five experts, limited trial testing (N = 30), and large-scale testing (N = 150). Content validity was analyzed using the Content Validity Ratio (CVR) and Content Validity Index (CVI). Empirical validity was determined through corrected item–total correlation (r_it), while reliability was assessed using Cronbach’s Alpha. The results showed that the instrument demonstrated strong content validity, indicated by a high CVI value. Empirical testing revealed three items (25, 34, and 37) that did not meet the r_it ≥ 0.30 criterion and were therefore removed. The final instrument consisted of 37 items with very high reliability (α = 0.939). This instrument is suitable for use as a measurement tool for assessing physics learning anxiety among senior high school students.